Penerapan Algoritma Dijkstra Dalam Menentukan Rute Terpendek pada TPA Mrican - Kuncoro, Fakih; Abdurrozzaq Zulkarnain, Ismail; Asrofi Buntoro, Ghulam (Universitas Islam Balitar, 2024)
This research explores the implementation of Dijkstra's Algorithm to determine the shortest route in waste management, particularly from Temporary Disposal Sites (TPS) to the Mrican Final Processing Site (TPA). With advancements in information technology, determining an efficient waste collection route is crucial for reducing operational costs, travel time, and fuel consumption. This study utilizes historical data and current road conditions to simulate routes, addressing challenges such as traffic congestion and unpredictable road conditions. Dijkstra's Algorithm has been proven effective in previous studies in transportation and logistics contexts, and is thus adopted in this study. The results show that applying this algorithm can enhance waste transportation efficiency, providing practical solutions for TPA Mrican management to optimize collection routes, reduce operational costs, and improve collection time efficiency.